PENERAPAN MODEL INSTRUCTIONAL GAMES MENGGUNAKAN HOT POTATOES UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA PADA MATERI EKOSISTEM (Penelitian Tindakakan Kelas SMP Negeri 2 Tanjungsiang-Subang) - Mia Nurwanti; R. Ading pramadi; Milla Listiawati (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2015)
Technology continues to developing along with the times require people to participate utilize these technologies in various fields, including education.T he teacher need to use a variation of instructional media to increase student mastery of concepts. Against the background of preliminary observations showed low student mastery of concepts, it can be seen based on the average value of the test results is 60 students daily test the average value is still below the minimum completeness criteria (KKM) set a school that is 75 This shows the low student mastery of concepts. Therefore, to improve students 'mastery of concepts then applied using a model of Instructional Games Hot Potatoes.Tujuan to be achieved, this study describes: a) the activities of teachers and students during the learning process b) Increasing students' mastery of concepts before implementation models using Hot Potatoes Instructional games each cycle c) students' mastery of concepts as applied to the model using the Hot Potatoes Instructional Games in the entire cycle, d) the attitude of students towards using models Instructional Games Hot Potatoes.Penelitian is classroom Action Research is located at SMP 2 Tanjungsiang class VII C amounts to 36 students.The instrument used in this study consisted of the test, namely: material ecosystem to determine students' mastery of concepts, teacher observation sheet activities and attitudes of students using a questionnaire. The results obtained by a) increasing student activity in each cycle, the highest student activity in the third cycle is 85% (high). Activity obtaining teacher during the learning process grounded in the learning stages planned b) Increasing students 'mastery of concepts in the first cycle to 65% (enough), Cycle II 75% (high) and cycle III 87% (high) c) students' mastery of concepts Instructional games after application of the model using the Hot Potatoes by 75% (high) d) students' attitudes toward models using Hot Potatoes Instructional games are overall positive. This is evident from the average score of the students' attitude scores greater than neutral attitude of students.Based on these results it can be concluded that the application of the Instructional games with hot potatoes can effectively improve the students' mastery of concepts